АБДУЛЛА ҚАҲҲОР ҲИКОЯЛАРИДА ПАРРАНДА ВА ҲАШОРАТЛАРГА ЎХШАТИШ - almamatova, shahnoza (FILOLOGIYA UFQLARI JURNALI, 2021)
The analogy serves as a basis for drawing scientific, philosophical, social, spiritual and enlightenment conclusions. Simulation is extremely important in the development of human thinking. This article discusses the skill of analogy and its role in the polishing of human speech, especially the skill of using analogy in Abdullah Qahhor’s stories, based on the analysis of the stories.